The challenge of longitudinal information: a "guided tour" on hierarchical modeling, tracking and missing information with a set of data from Muzambinho study - Maia, José António Ribeiro (2010)
The main aim of this study is to present a tutorial to Sport Sciences and Physical Education researchers when facing challenges emerging from longitudinal data analysis. Based on a real data set from Muzambinho mixed-longitudinal study, we shall deal with three main concerns: 1) to build a developmental view based on hierarchical or multilevel modeling; 2) to present two solutions to the missing data problem; 3) to search for stability of interindividual differences in intraindividual change (i.e., tracking). In each of these main issues questions will be asked whose answers will be presented alongside with main results coming from different statistical softwares used.